Effects of Different Species of Pepper (Capsicum) on Oxidative Stability of Raw and Cooked Pork Patties - Olorunsanya, A.O.; Olorunsanya, E.O.; Aliu, O.T.; Kayode, R.M.O. (Pakistan Journal of Nutrition, 2009)
Antioxidant properties of different species of pepper (Capsicum) were evaluated in pork patties from two weeks frozen pork. In 200 g pork patties was added 1.5 % cayenne, bell, tobasco or habenero pepper and a control. A positive reference control was prepared with 200 mg of α-tocopherol acetate in 200 g of pork patties. The preparations were made for raw and cooked samples. The addition of any specie of pepper in the patties showed a better antioxidative property (p<0.05) than the α-tocopherol acetate for raw and cooked samples. Cayenne pepper exhibited the best antioxidant property of all the pepper species studied. The control samples had the worst lipid deterioration.